Lifting the Gate: Evaluation of Supplemental Instruction Program in Chemistry - Duyen Pham; Li Ye (MDPI AG, 2024)
College-level introductory chemistry has a high impact for predicting students' early success and long-term academic outcomes. Students from traditionally underserved communities are disproportionately held back in this course. To improve student success, the Supplemental Instruction (SI) program at a public four-year Hispanic-serving institution was revamped from a voluntary option to a co-requisite for the introductory chemistry course. The study evaluates the effectiveness of the new format of SI program and explores associated factors contributing to the impacts of the program. Students with or without SI were compared through multiple quantitative metrics, including course GPA, final exam score, DFW rate, and pass rate. Data analysis showed that students who completed SI with credit obtained 0.9 higher average course GPA than their counterparts and performed significantly better on all the other metrics. More importantly, the equity gaps between underserved and better-served students were narrowed down. Furthermore, students who took introductory chemistry with SI still obtained 0.3 higher average course GPA in their subsequent General Chemistry I course than those without it. The findings suggested that incorporating the SI into introductory chemistry as co-requisite is necessary and effective to improve students' success and narrow down the equity gaps in gateway chemistry courses.